The Effect of Selenium on Rice Quality Under Different Nitrogen Levels - Yuqi Liu; Bingchun Yan; Ya Liu; Yuzhuo Liu; Liqiang Chen; Hongfang Jiang; Yingying Feng; Jiping Gao; Wenzhong Zhang (Agronomy, 2025)
Selenium (Se) is a trace element that is beneficial in enhancing the quality of rice production. However, research on the effects of Se on rice quality under varying nitrogen (N) levels is limited and requires further investigation. This experiment utilized a randomized block design, incorporating an N fertilizer reduction and efficient application mode, with two N levels, CN (225 kg·hm−2) and LN (180 kg·hm−2), and three Se levels, HSe (0.12 kg·hm−2), LSe (0.06 kg·hm−2), and 0Se (0.00 kg·hm−2). The results indicated that the effects of Se on rice processing quality differ under different N levels. Selenium adversely affected the processing quality under the CN level, whereas it demonstrated some improvement at the LN level. Furthermore, Se application increased the Se content in rice by 46.48–141.82% and enhanced the taste value by 14.88–22.73%. It significantly improved the nutritional and cooking qualities of rice and positively influenced its appearance. Although N levels induced variations, their overall impact remained beneficial. Considering various indicators, applying 0.06 kg·hm−2 of Na2SeO3 under the LN level yielded optimal results. This study provides valuable insights into the effects of Se on rice quality under different N levels. It provides a more scientific basis for the application of selenium fertilizer in rice.